Freedom Soup - Charles, Tami (Somerville, Massachusetts : Candlewick Press, 2019)
"Every year, Haitians all over the world ring in the new year by eating a special soup, a tradition dating back to the Haitian Revolution. This year, Ti Gran is teaching Belle how to make the soup -- Freedom Soup -- just like she was taught when she was a little girl. Together, they dance and clap as they prepare the holiday feast, and Ti Gran tells Belle about the history of the soup, the history of Belle's family, and the history of Haiti, where Belle's family is from."--
Keywords: Haitians -- Foreign countries -- Juvenile fiction; Soups -- Juvenile fiction